Neutron reflection from a liquid helium surface: Жидкий гелий - Charlton, T.R.; Dalgliesh, R.M.; Ganshin, A.; Kirichek, O.; Langridge, S.; McClintock, P.V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The reflection of neutrons from a helium surface has been observed for the first time. The 4He surface is smoother in the superfluid state at 1.54 K than in the case of the normal liquid at 2.3 K. In the superfluid state we also observe a surface layer 200 Å thick which has a subtly different neutron scattering cross-section, which may be explained by an enhanced Bose–Einstein condensate fraction close to the helium surface. The application of neutron reflectometry described in this paper creates new and exciting opportunities for the surface and interfacial study of quantum fluids.